Reconstruction of an alveolar cleft for orthodontic tooth movement - (:unkn) unknown (My University, 2000)
Bone grafting to repair an alveolar cleft has long been an integral part of the treatment of persons with unilateral and bilateral clefts of the lip and alveolus. The presence of the cleft places a limitation on the orthodontist who would like to move teeth in the area of the cleft. Various grafting materials have been placed in alveolar clefts in an attempt to solve this problem. The case to be presented is a patient with a Class II, Division 2, malocclusion with a left unilateral alveolar cleft and a repaired cleft lip. Ten months after initiating orthodontic treatment, a free gingival graft procedure was performed because of insufficient vestibular depth and the narrow width of the keratinized attached gingiva at the left maxillary lateral and central incisor region. Two months after periodontal surgery, a mix of decalcified freeze-dried bone allograft and a granular bioactive glass graft material (1:1) were applied subperiostally on the buccal aspect of the edentulous cleft region. Six months later, the teeth adjacent to the grafted alveolar cleft were orthodontically moved into the edentulous area. The treatment results indicated that orthodontic, periodontal, and surgical interventions resulted in a successful closure of the alveolar cleft as well as improved periodontal conditions of the teeth adjacent to the cleft area. From the orthodontic point of view, tooth movement can be achieved successfully into a bone graft made of freeze-dried bone and bioactive glass.
Keywords: Humans; Adolescent; Male; Alveolar Process; Alveoloplasty; Bone Transplantation; Cleft Lip; Cleft Palate; Combined Modality Therapy; Esthetics, Dental; Malocclusion, Angle Class II; Maxilla; Orthodontics, Corrective; Patient Care Planning; Tooth Movement Techniques